Quality Assurance of Administrative Judiciary: Perspectives from France - Abuirmilah, Bassam; Zubaidi , Khalid Al; El-Manaseer , Suhaib Ahmad (Journal of Ecohumanism, 2024)
Objective: This study objective is necessary to understand the concepts related to quality in the administrative judiciary: perspectives from France. The current study also identifies the main requirements for achieving quality in the administrative judiciary function. Method: The study embraces the descriptive and analytical approaches in order to identify and analyze the concepts and measures of quality that are compatible with the nature and specificity of administrative cases. Results and conclusion: The study has reached some results, the most important of which are: The real measure of quality in the administrative judiciary is represented as the achievement of the strategic objective of the administrative judiciary. Another result turns out to be that the quality of the performance of the administrative judiciary, whether quantitative or qualitative, is, in fact, just a means to achieve this goal.